Writings of Brazility: subjectivation and lusophone policy in the documentation of the vernacular - Magalhães, Anderson Salvaterra (2014)
The aim in this paper is to demonstrate how writing about Brazil simultaneously founds and is founded by values determinant of discourses which build the sense of a vernacular. Two documents are analyzed: Pero Vaz de Caminha’s “Letter”, a key piece of writing for the production of the discourse of Brazility, and Oswald de Andrade’s poem “Erro de português”, a reformulation of the founding piece of writing. The ethical implication of the aesthetic accomplishment of the two pieces of writing in Portuguese articulates subjectivation processes which define possible cultural identities and actualizes a language policy which conveys tension between the genitive and locative character of the vernacular, respectively, of Brazil and in Brazil.